Hope and strength in the Western Balkans - Rivellini, Matteo (European Investment Bank, 2020)
The Western Balkans have been a crossing point between Central Europe and the East for centuries. Devastated by tragic conflicts, nationalism and neglected investments, the Western Balkan countries are striving to find a new equilibrium. Citizens and institutions in the Balkans have repeatedly affirmed their ambition to become part of the European Union and have made significant efforts to turn this dream into reality. The European Investment Bank (EIB) has done a lot in this region over the past 20 years. It has helped build pan-European transport corridors, supported direct foreign investment, helped redevelop urban areas, provided technical assistance and additional finance to enhance and develop social and economic infrastructure, and stimulated private sector growth to create jobs. Looking ahead, there is hope for a brighter and greener future for the Western Balkans. Matteo Rivellini is the Head of Division in charge of lending operations in Slovenia, Croatia and the Western Balkans at the EIB. This is the thirteenth essay in the Big Ideas series created by the European Investment Bank.
Description based on print version record.
KU Open Services
Keywords: Business & Economics / Economics; Economics; Electronic books